The room-temperature crystallisation of a one-dimensional gallium fluorophosphate, Ga(HPO4)(2)F center dot H3N(CH2)(3)NH3 center dot 2H(2)O, a precursor to three-dimensional microporous gallium fluorophosphates - Walton, R; Millange, F; Le Bail, A; Loiseau, T; Serre, C; O'Hare, D; Ferey, G (2000)
The one-dimensional gallium fluorophosphate Ga(HPO4)2F·H3N(CH2)3NH3.2H2O 1 crystallises at room temperature from an aqueous mixture of Ga2O3, H3PO4, 1,3-diaminopropane, and HF; compound 1 converts to the three-dimensional microporous fluorophosphate ULM-3 on heating to 160 °C under hydrothermal conditions.